On being ignored. Issue 4 (15th April 2021) - Wu, Joyce
Abstract: Racism in universities to be best described as "being ignored." This means not having complaints heard, or having your existence and identities overlooked. Being ignored is a powerful tool used by racist institutions to suppress experiences of race and gender inequality. Being ignored is also an effective way to undermine your sense of self and the validity of your experience. This alternative narrative is a typology of the types of ignoring that goes on at the higher education—read and see how many types of ignoring you can relate with!